Anti-Acne Activity From Biocellulose Mask Formula Containing (Aloe Vera (L.) Burm.F) Essence Combined With Vitamin E - Fitri, Raissa; Reveny, Julia; Harahap, Urip; Dharmawan, Hariyadi; Nasri (Indonesian Journal of Pharmaceutical and Clinical Research, 2021)
Abstract. Biocellulose mask sheet is a new found pharmaceutical cosmetic design that widely commercial. Mostly due to it’s biodegradable properties, provide an eco-friendly waste. Combination of Aloe vera essence (AE) and Vit E to provide and determine it’s respective anti-acne properties in biocellulose mask form. Formulation of biocellulose mask with the help of Acetobacter xylinum bacteria varied with different formulae: F1 (Vitamin E 1%), F2 (E 2.5 %), F3 (AE 5%), F4 (AE 2.5%+Vit E 1%) and F5 (AE 5%+Vit E 1%) followed antimicrobials test with common acne bacteria by diffusion disk against Propionibacterium acne (PAC) ATCC 6919 and Pseudomonas aeruginosa (PAA) ATCC 27853. Study revealed that each formulae design F1; F2; F3; F4; F5 tested against PAC diffusion disk resulted 7.86; 11.67; 10.13; 112.10; 10.33 mm respectively. As for PAA diffusion disk resulted 7.76; 11.63; 10.33; 11.67; 11.00 mm respectively. Biocellulose mask containing combination of AE 2.5% and Vit E (F4) would provide the best anti-acne activity amongst other formulae.